2015
DOI: 10.1126/science.aab0551
|View full text |Cite
|
Sign up to set email alerts
|

Cortical information flow during flexible sensorimotor decisions

Abstract: During flexible behavior, multiple brain regions encode sensory inputs, the current task, and choices. It remains unclear how these signals evolve. We simultaneously recorded neuronal activity from six cortical regions (MT, V4, IT, LIP, PFC and FEF) of monkeys reporting the color or motion of stimuli. Following a transient bottom-up sweep, there was a top-down flow of sustained task information from frontoparietal to visual cortex. Sensory information flowed from visual to parietal and prefrontal cortex. Choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
422
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(484 citation statements)
references
References 37 publications
58
422
4
Order By: Relevance
“…However, the critical question for this study was where the feature selection effects emerged the earliest, and that appears to be VPA. Consistent with our findings, a recent study in which monkeys reported the color or motion of foveally presented stimuli found that choice signals developed in lateral prefrontal cortex and parietal regions and were fed back to FEF and sensory cortex (Siegel et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…However, the critical question for this study was where the feature selection effects emerged the earliest, and that appears to be VPA. Consistent with our findings, a recent study in which monkeys reported the color or motion of foveally presented stimuli found that choice signals developed in lateral prefrontal cortex and parietal regions and were fed back to FEF and sensory cortex (Siegel et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…84 units for monkey C and 43 units for monkey R) showed significant SFC with the nearby LFP during the baseline epoch (the 500 ms preceding the target onset), and 119 units (79%; 78 units for monkey C and 41 units for monkey R) showed significant SFC during the choice epoch (200-700 ms after target onset). We found prominent SFC with a peak in the beta-frequency range (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) [permutation tests, familywise error probability (P FWER ) < 0.05] (Fig. 2 A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Firing rates of neurons in the PPC encode movement intention and the temporal evolution of movement choices (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) as well as decision variables such as expected rewards, the subjective desirability during reward-guided decisions (14)(15)(16)(17)(18), and the certainty in perceptual decisions (19). Decisions are made within a network that extends across many regions of the brain (20)(21)(22)(23)(24)(25), so efficient and flexible mechanisms are required to enable distributed computations. Dynamic and frequency-specific correlations in activity between brain areas are ubiquitous and offer potential physiological mechanisms supporting distributed computations in decision networks (13,21,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…Finally, empirical functional connectivity studies have shown that modules are weakly functionally connected to each other, likely because their computations are predominantly distinct, suggesting modular function (6,7,16,36,79). However, connections do occur between modules that transfer information between the modules and influence local activity in the modules, potentially increasing the modules' computational loads (6,7,16,27,28,36,(80)(81)(82)(83). Thus, to validate the autonomous nature of modules, it is necessary to demonstrate that, as more modules are engaged simultaneously and more information is generated across the network and transferred between the modules, the modules' computational loads do not increase (50,51,53) (Fig.…”
Section: Discussionmentioning
confidence: 99%